Exploring trends and tropes in young adult fantasy literature from the U.S. since 2005 - Beestone, Kelly (2023)
This thesis contends that YA fantasy fiction continuously evolves to adapt to its ageing readership, calls for more diversity, and a circuitous relationship between publishers, authors, and content creators which enables fans to participate in the formation of a YA canon distinct from traditional fantasy literature. The first chapter examines the creation of the YA community, exploring how it mimics the behaviours and practices of other fandoms, including gatekeeping membership through cultural capital. This chapter serves as a foundation for the chapters that follow, which each consider close-reading analysis of case study texts alongside paratextual and fan-created sources. Chapter 2 looks at the role of the female protagonist in three YA series: Leigh Bardugo’s Shadow and Bone (2012), Marie Lu’s The Young Elites (2014), and Susan Dennard’s Truthwitch (2016), acknowledging how the novels challenge pseudo-medieval models of fantasy literature through myth-making centering female protagonists. Chapter 3 explores the romanticisation of toxic masculinity in Sarah J. Maas’ popular A Court of Thorns and Roses (2015) trilogy, contending that it normalises hegemonic masculinity by comparing the protagonist’s two love interests and by drawing on fairy tales and Greek mythology. In Chapter 4, I consider how Tomi Adeyemi discusses race and the Black Lives Matter movement in America through her Nigeria-inspired novel Children of Blood and Bone (2018), arguing that she uses allegory in her narrative alongside paratextual and epitextual sources such as interviews and author’s notes in an attempt to educate readers on police brutality in the U.S. Finally, in Chapter 5, I consider how in the Shades of Magic trilogy (2015) V.E. Schwab attempts to create a fantasy setting where queer characters are able to live without fear of discrimination, and how her experiences as an LGBTQ+ author complicate this goal, creating a tension between authorial intention and reader responses.